Arabidopsis Tubby-like proteins : Subcellular localization and participation in stress signaling and mutualistic interactions - Reitz, Marco Uwe; Justus Liebig University Giessen (My University, 2012)
TUBBY and Tubby-like proteins (TLPs) have first been described in mice, where mutations in respective genes lead to severe disease phenotypes. Mouse TUBBY was shown to be targeted to the plasma membrane (PM) in transfected cells by specific phosphatidylinositol 4,5-bisphosphate (PIP2) binding. Several neuro-transmitters elicited dislodgement of TUBBY from the PM in a phospholipase C (PLC) dependent manner, which led to a translocation of the protein into the nucleus. There, it was suggested to function as transcriptional regulator. Mammalian TLPs have also been implicated to work in vesicular trafficking, insulin signaling and as extracellular bridging molecules in phagocytosis. Since their first description, TLPs have been detected in the genomes of a multitude of eukaryotic organisms, including plants. The conservation throughout so many species suggests fundamental biological functions. In higher plants, 11 TLPs were identified in the model species Arabidopsis thaliana where AtTLP9 was implicated to act in abscisic acid signaling. In addition, results from other plant species suggest roles for TLPs in biotic interactions and abiotic stress signaling. In this study, a delayed colonization of attlp mutant lines by the mutualistic fungus Piriformospora indica was observed. As no increased immune reactions were detected in the mutant lines, AtTLPs might constitute compatibility factors needed by P. indica in the early interaction with Arabidopsis roots. Further studies were carried out to investigate the subcellular localization of plant TLPs. GFP-tagged AtTLP3 was detected at the PM in cells transiently over-expressing the protein. The obtained results suggest a conservation of the PIP2 binding capacity as origin of AtTLP3 PM targeting. Moreover, H2O2 triggered a specific, PLC dependent re-localization of the protein, possibly activating further downstream responses. In contrast to mouse TUBBY, a plastidial and nucleo-cytosolic localization was observed for the N-terminal part of AtTLP3. It is tempting to speculate that AtTLP3 translates rises in H2O2 levels into intracellular signaling. Taken together, this study shed further light on this relatively unexplored gene family in Arabidopsis, supporting the proposed roles of TLPs in abiotic and biotic stress signaling. In addition, the response of AtTLP3 to H2O2 provides an interesting new direction for further research on plant TLPs.

TUBBY und die verwandten Tubby-like Proteine (TLPs) wurden zuerst in Mäusen (Musmusculus) beschrieben, wo Mutationen in den entsprechenden Genen schwere Krankheitssyndrome hervorrufen. MmTUBBY wurde der Plasmamembran (PM) nachgewiesen. Als Ursprung für diese Lokalisation wurde eine spezifische Interaktion des Proteins mit Phosphatidylinositol 4,5-biphosphat (PIP2) in der Membran identifiziert. Applikation verschiedener Neurotransmitter führte zu einer Phospholipase C (PLC) abhängigen Freisetzung des Proteins von derPM und zur Akkumulation im Zellkern, wo es möglicherweise an der Genregulation beteiligt ist.Weitere Funktionen von TLPs in Säugetieren wurden in der Regulation von vesikulärem Transport, der Phagocytose und im Insulin Signalweg beschrieben.TLPs wurden in den Genomen einer Vielzahl eukaryotischer Organismen identifiziert, was auf essentielle Funktionen dieser Proteinfamilie hindeutet. 11 TLPs wurden in der Modellpflanze Arabidopsis thaliana beschrieben, wo AtTLP9 eine Rolle in der Signaltransduktion von Abscisinsäure zu spielen scheint. Ergebnisse aus anderen Pflanzen deuten auf Funktionen pflanzlicher TLPs in biotischen Interaktionen und in der Reaktion auf abiotischen Stress hin.In der vorliegenden Studie konnte eine verspätete Besiedlung von attlp Mutantenlinien durch den mutualistischen Pilz Piriformospora indica gezeigt werden. Da keine erhöhten Immunreaktionen in den Mutanten nachgewiesen wurden, könnten AtTLPs als Kompatibilitätsfaktoren dienen, die von P. indica in der frühen Interaktion mit Wurzeln von Arabidopsis benötigt werden. WeitereExperimente dienten der Untersuchung der subzellulären Lokalisation pflanzlicher TLPs. GFPgekoppeltes AtTLP3 wurde nach transienter Überexpression an der PM von Zellen beobachtet.Die erhaltenen Ergebnisse deuten auf eine Konservierung der PIP2 Interaktion als Ursprung für die beobachtete Lokalisation hin. Zugabe von H2O2 führte zu einer spezifischen PLC abhängigen Freisetzung des Proteins von der PM. Im Gegensatz zu MmTUBBY, wurde der N-terminale Bereich von AtTLP3 in Plastiden, dem Cytosol und dem Zellkern detektiert. Es bleibt zu untersuchen, ob AtTLP3 Anstiege in H2O2 Konzentrationen in intrazelluläre Signale umwandelt.Zusammengenommen liefert die vorliegende Studie neue Erkenntnisse über diese bis jetzt nur wenig in Pflanzen beschriebene Proteinfamilie in Arabidopsis. Die erhaltenen Ergebnisse unterstützen die Annahme, dass TLPs an Reaktionen auf biotischen und abiotischen Stress beteiligt sind. Zusätzlich liefert die Relokalisation von AtTLP3 als Antwort auf H2O2 einen interessanten neuen Ansatz zur Erforschung pflanzlicher TLPs.
Tubby-like Proteine in Arabidopsis : subzelluläre Lokalisation und Beteiligung an Stressantworten und mutualistischen Interaktionen
Keywords: ddc:570